Slow modes in the Hermean magnetosphere: Effect of the solar wind hydrodynamic parameters and IMF orientation - Varela, J.; Pantellini, F.; Moncuquet, M. (Planetary and Space Science, 2016)
International audience The aim of this study is to simulate the slow mode structures in the Hermean magnetosphere. We use a single fluid MHD model and a multipolar expansion of the Northward displaced Hermean magnetic field, to perform simulations with different solar wind parameters to foreseen the most favorable configuration for the formation of slow modes, attending to the solar wind density, velocity, temperature and the interplanetary magnetic field orientation. If the interplanetary magnetic field is aligned with the Mercury-Sun direction, the magnetic axis of Mercury in the Northward direction or the planet orbital plane, slow mode structures are observed nearby the South pole. If the orientation is in the Sun-Mercury or Northward directions, slow mode structures are observed nearby the North pole, but smaller compared with the structures near the South pole. Increasing the density or the solar wind velocity avoids the formation of slow modes structures, not observed for a dynamic pressure larger than 6.25 ·10-9 Pa in the case of a Northward interplanetary magnetic field orientation, due to the enhancement of the bow shock compression. If the solar wind temperature increases, the slow mode structures are wider because the sonic Mach number is smaller and the bow shock is less compressed.